MNP hyperthermia and hypofractionated radiation activate similar immunogenetic and cytotoxic pathways. (1st January 2020) - Duval, Kayla E. A.; Petryk, James D.; Crary-Burney, Margaret A.; Demidenko, Eugene; Wagner, Robert J.; Hoopes, P. Jack
Abstract: Objective: The goal of this study is to better understand the immunogenetic expression and related cytotoxic responses of moderate but clinically relevant doses of hypofractionated radiation (1x15 Gy and 3x8 Gy) and magnetic nanoparticle hyperthermia (mNPH, CEM43 30) Methods: Genetic, protein, immunopathology and tumor growth delay assessments were used to determine the immune and cytotoxic responses following radiation and mNPH alone and in combination. Although the thermal dose used, 43 C°/30 min (CEM43 30), typically results in modest independent cytotoxicity, it has shown the ability to stimulate an immune response and enhance other cancer treatments. The radiation doses studied (15 Gy and 3x8 Gy) are commonly used in preclinical research and are effective in selected stereotactic and palliative treatment settings, however they are not commonly used as first-line primary tumor treatment regimens. Results: Our RNA-based genetic results suggest that while many of the cytotoxic and immune gene and protein pathways for radiation and hyperthermia are similar, radiation, at the doses used, results in a more consistent and expansive anti-cancer immune/cytotoxic expression profile. These results were supported by immunohistochemistry based cytotoxic T-cell tumor infiltration and tumor growth delay studies. When used together radiation and hyperthermia led to greater immune and cytotoxic activity than either modality alone. Conclusion: This study clearly shows that modest, but commonly used hypofractionated radiation and hyperthermia doses share many important immune and cytotoxic pathways and that combining the treatments, as compared to either treatment alone, results in genetic and biological anti-cancer benefits.